COP9 signalosome complex subunit 5, an IFT20 binding partner, is essential to maintain male germ cell survival and acrosome biogenesis. Issue 1 (2nd August 2019) - Huang, Qian; Liu, Hong; Zeng, Jing; Li, Wei; Zhang, Shiyang; Zhang, Ling; Song, Shizhen; Zhou, Ting; Sutovsky, Miriam; Sutovsky, Peter; Pardi, Ruggero; Hess, Rex A; et al.
Abstract: Intraflagellar transport protein 20 (IFT20) is essential for spermatogenesis in mice. We discovered that COPS5 was a major binding partner of IFT20. COPS5 is the fifth component of the constitutive photomorphogenic-9 signalosome (COP9), which is involved in protein ubiquitination and degradation. COPS5 is highly abundant in mouse testis. Mice deficiency in COPS5 specifically in male germ cells showed dramatically reduced sperm numbers and were infertile. Testis weight was about one third compared to control adult mice, and germ cells underwent significant apoptosis at a premeiotic stage. Testicular poly (ADP-ribose) polymerase-1, a protein that helps cells to maintain viability, was dramatically decreased, and Caspase-3, a critical executioner of apoptosis, was increased in the mutant mice. Expression level of FANK1, a known COPS5 binding partner, and a key germ cell apoptosis regulator was also reduced. An acrosome marker, lectin PNA, was nearly absent in the few surviving spermatids, and expression level of sperm acrosome associated 1, another acrosomal component was significantly reduced. IFT20 expression level was significantly reduced in the Cops5 knockout mice, and it was no longer present in the acrosome, but remained in the Golgi apparatus of spermatocytes. In the conditional Ift20 mutant mice, COPS5 localization and testicular expression levels were not changed. COP9 has been shown to be involved in multiple signal pathways, particularly functioning as a co-factor for protein ubiquitination. COPS5 is believed to maintain normal spermatogenesis through multiple mechanisms, including maintaining male germ cell survival and acrosome biogenesis, possibly by modulating protein ubiquitination. Abstract : Summary Sentence COPS5 is essential for mouse spermatogenesis and particularly in maintaining male germ cell survival and acrosome biogenesis.